The contrast‐to‐noise ratio for image quality evaluation in scanning electron microscopy. Issue 1 (22nd December 2014) - Timischl, F.
Summary The contrast‐to‐noise ratio (CNR) is presented and characterized as a tool for quantitative noise measurement of scanning electron microscope (SEM) images. Analogies as well as differences between the CNR and the widely used signal‐to‐noise ratio (SNR) are analytically and experimentally investigated. With respect to practical SEM image evaluation using the contrast‐to‐noise ratio, a standard specimen and an evaluation program are presented. SCANNING 37:54–62, 2015. © 2014 Wiley Periodicals, Inc.